2012
DOI: 10.3762/bjoc.8.124
|View full text |Cite
|
Sign up to set email alerts
|

Formation of smectic phases in binary liquid crystal mixtures with a huge length ratio

Abstract: SummaryA system of two liquid-crystalline phenylpyrimidines differing strongly in molecular length was studied. The phase diagram of these two chemically similar mesogens, with a length ratio of 2, was investigated, and detailed X-ray diffraction and electrooptical measurements were performed. The phase diagram revealed a destabilization of the nematic phase, which is present in the pure short compound, while the smectic state was stabilized. The short compound forms smectic A and smectic C phases, whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Molecular packing efficiency between layers is disrupted favoring the OLFs with same interdigitation levels between molecules. Non‐tilted SmB is favored over SmC mesophase for bromine‐terminated, while tilted SmC is favored over SmB mesophase for hydroxyl‐terminated ILCs, as predicted by previous work …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Molecular packing efficiency between layers is disrupted favoring the OLFs with same interdigitation levels between molecules. Non‐tilted SmB is favored over SmC mesophase for bromine‐terminated, while tilted SmC is favored over SmB mesophase for hydroxyl‐terminated ILCs, as predicted by previous work …”
Section: Resultssupporting
confidence: 85%
“…The results indicated that the stability of smectic phase decreases with the increasing length difference between the two molecules. From those results, an optimum length was suggested around 1.8 to maximize the stability of the smectic state …”
Section: Introductionmentioning
confidence: 99%
“…For films containing 10, 25, and 50 wt% CL, a layer spacing of 4.05 (q=1.55 nm -1 ), 4.40 (q=1.43 nm -1 ) and 4.82 nm (q=1.30 nm -1 ) was found, respectively ( Figure 2), which can be directly linked to the d-spacing of the individual compounds and their respective amounts (Figure 2e, dashed line). [33][34][35] The polymer film containing 10 wt% CL displays a weak small angle signal that is split-up and is extremely broad, which suggests the demixing of 6SzMA•6OB and CL occurs. The wide angle area of the 2D x-ray scattering patterns (Figure 2a-c) show lobes located at q ≈14 nm −1 which become narrower and more intense with increasing cross-link density suggesting that the orientational order is increasing (Figure 2f).…”
Section: Preparation and Characterization Of Lcnsmentioning
confidence: 99%
“…Experiments have shown that in binary mixtures of LCs with a chemically similar core but different length of the (semi-)flexible tail, the smectic phase can become stabilized at the cost of the nematic phase if the length ratio of the tails is increased. 6,7,73 Since these results could well be an artifact of increased flexibility of the molecules, it would be interesting to test by experiments/molecular simulations if this stabilization of the smectic phase also occurs when only the length ratio of the rigid cores is increased. The LCs used in such a study should be of nematic type.…”
Section: Solubility Of Hard-sphere Solutes In Linear and Partiallymentioning
confidence: 99%